Do Politicians Affect Firm Outcomes? Evidence from Connections to the German Federal Parliament - André Diegmann; Laura Pohlan; Andrea Weber (CESifo GmbH, 2025)
We study how connections to German federal parliamentarians affect firm dynamics by constructing a novel dataset linking politicians and election candidates to the universe of firms. To identify the causal effect of access to political power, we exploit (i) new appointments to the company leadership team and (ii) discontinuities around the marginal seat of party election lists. Our results reveal that connections lead to reductions in firm exits, gradual increases in employment growth without improvements in productivity. Adding information on credit ratings, subsidies and procurement contracts allows us to distinguish between mechanisms driving the effects over the politician's career.
Keywords: O43; L25; D72; 330; politicians; firm performance; identification; political connections